2019
DOI: 10.1093/cvr/cvz244
|View full text |Cite
|
Sign up to set email alerts
|

A novel secreted-cAMP pathway inhibits pulmonary hypertension via a feed-forward mechanism

Abstract: Aims Cyclic adenosine monophosphate (cAMP) is the predominant intracellular second messenger that transduces signals from Gs-coupled receptors. Intriguingly, there is evidence from various cell types that an extracellular cAMP pathway is active in the extracellular space. Herein, we investigated the role of extracellular cAMP in the lung and examined whether it may act on pulmonary vascular cell proliferation and pulmonary vasculature remodelling in the pathogenesis of pulmonary hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Similar to our observations, these authors demonstrated, in human PASMCs, that nutlin-3 induces cell growth arrest but not apoptosis, whereas whether nutlin-3 has any anti-inflammatory effect in the lungs has not been tested. Studies from other groups have also demonstrated that restoration of p53 functions may underlie the observed therapeutic effects by various interventions in experimental PAH (Abid et al, 2014;Jones et al, 2020). Nevertheless, it should be noted that smooth muscle cells are unlikely to be the only effector cell in vivo which mediate the beneficial effects of CX-5461 and p53 activation.…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our observations, these authors demonstrated, in human PASMCs, that nutlin-3 induces cell growth arrest but not apoptosis, whereas whether nutlin-3 has any anti-inflammatory effect in the lungs has not been tested. Studies from other groups have also demonstrated that restoration of p53 functions may underlie the observed therapeutic effects by various interventions in experimental PAH (Abid et al, 2014;Jones et al, 2020). Nevertheless, it should be noted that smooth muscle cells are unlikely to be the only effector cell in vivo which mediate the beneficial effects of CX-5461 and p53 activation.…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lmentioning
confidence: 99%
“…In particular, reduced p53 protein in PASMCs may be implicated in the aberrant proliferation of the cells found in PAH (Jones et al, 2020;Wang et al, 2019). Restoration of the normal p53 functions has been linked to therapeutic effects on PAH in animal models (Abid et al, 2014;Jones et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nox1/Ref-1-mediated activation of CREB promotes gremlin1-driven endothelial cell proliferation and migration in sugen5416 + hypoxia-induced PH model [ 8 ]. However, the role of CREB in pulmonary vascular remodeling remains elusive, because either of the increased and reduced CREB expression has been proposed to mediate PASMCs proliferation in pulmonary vascular remodeling [ 9 13 ]. Additionally, the regulatory signaling of CREB activation in PASMCs proliferation has not been well characterized in PH.…”
Section: Introductionmentioning
confidence: 99%
“…Although conventional therapies reduce the symptoms of PAH by leveraging three distinct pathways involved in the vasoconstriction and vasodilation imbalance, none of the approved therapies have shown satisfactory results in reversing PAH. Accumulating clinical evidence suggests that the shortcoming of current treatments may be due to the multifactorial nature of PAH and the genetic variations among patients [ 126 , 127 , 128 , 129 , 130 , 131 ].…”
Section: Precision Medicinementioning
confidence: 99%